RELATIONSHIP BETWEEN ARBOREAL, TOPOGRAPHIC, AND EDAPHIC STRUCTURES IN A STRETCH OF A RIPARIAN FOREST IN THE PAMPA BIOME, RIO GRANDE DO SUL, BRAZIL - Bentancor Araujo, Ana Claudia; Bentancor Araujo, Helio Junior; Grimm, Edenir Luis; Longhi, Solon Jonas (Floresta, 2019)
Despite the considerable loss of natural area in the Pampa biome, the number of scientific studies carried out here is low; it is lower in terms of natural regeneration. Therefore, the present study analyzed arboreal shrub and natural regeneration as well as the influence of environmental variables on the distribution of a riverine forest of the Espinilho stream in the Pampa biome, Rio Grande do Sul. A hundred plots were systematically set for arboreal shrub sampling. To evaluate the regenerating component, two classes were established: Class I and Class II. The main species in the arboreal shrub were Ocotea acutifolia (Nees) Mez and Pouteria salicifolia (Spreng.) Radlk., while those in natural regeneration were Eugenia uniflora L. and Blepharocalyx salicifolius (Kunth) O.Berg. The characteristics of the relief, soil, and canopy conditioned the species of the arboreal shrub and regenerating strata.